Determinants of English Language Proficiency of Freshmen Education Students - Daianne, Daianne S. (Future Science / FSH-PH Publications, 2022)
This research aimed to identify the different student-related and teacher-related factors that influence the English language proficiency of freshmen students enrolled in the College of Education of a university in the Province of Bulacan for School Year 2018 – 2019. It looked into their level of proficiency as to gender, tracks and strands, type of school, honors received and language exposure. It also identified four (4) teacher-related factors like gender, educational attainment, teaching experiences and teaching styles. The descriptive correlational research method was employed. There were three (3) standardized instruments used in gathering the necessary data. Mean, Pearson r, and Multiple Regression Analysis were used to generate the findings of the study. The findings revealed that the freshmen education students’ English language proficiency level is at Intermediate level. It also revealed that gender, track and strand, type of school, and honors received do not significantly influence the students’ proficiency level. However, some language exposure indicators revealed an influence in varying extent. The study also revealed two (2) teacher-related factors are influential and these are teaching experience and teaching styles. Gender and educational attainment of the teachers were found correlated but not to a significant extent.